ESCALATING INTERNATIONAL STUDENTS' INTERACTIVITY USING THE DST APPROACH - Rahmawati, Yusi; Hidayat, Eko Nur (Tomorrow's Education Journal, 2024)
An active and healthy classroom offline and online should run simultaneously two ways of communication to counterbalance the communication between the lecturer and the students inside. In running the communication of a lesson, a lecturer has a responsibility to anticipate the emptiness or the lack of a communicative environment during the teaching-learning process. Digital Story Telling is an approach that can be used by lecturers in teaching to escalate the students’ interactivity because they will be challenged to speak up individually, can be randomly speaking, and everybody will get an opportunity to share their story about a certain topic. In this research, the researcher would like to observe how can DST approach escalates international students’ interactivity. The research method used by the researcher is a narrative inquiry to record the objects’ activities and experiences of an individual or a small group concerned with stories shared by the research objects. There are some important things underlying this research; they are by implementing the DST approach, the international students felt challenged by the lecturer to speak up and it stimulated the international students to emerge their initiative to share their experiences digitally.